The impact of ancient Mesoamerican cities on long-term environmental sustainability: the view from historical ecology - Antorcha-Pedemonte, Ricardo; Rivera-Núñez, Tlacaelel; Fargher-Navarro, Lane F. (Frontiers in Ecology and Evolution, 2023)
The impact of ancient urban occupa;ons on sustainability has recently become a topic of interests for archaeologists, as well as many other scholars. Much of this archaeological research has focused on documen;ng the longevity of ancient ci;es and elucida;ng the social and economic strategies that were employed at the urban and regional scales to promote urban sustainability. In this ar;cle, we add to this discussion by coming at the issue of sustainability by considering the impact of the environmental legacies leV by ancient ci;es aVer their abandonment. Using a series of cases from pre-Hispanic Mesoamerica (OMYK (Coba), Kiuic, Lagunas de Yalahau, and Tlaxcallan), we show through ethnoecological and historic ecological research that in some cases pre-Hispanic people, living in urban zones, affected "intermediate" disturbances that increased biodiversity, biomass, and sustainability by crea;ng second natures that have endured for centuries. Introduc4on Since its introduc;on in wider academic debates in the early 1970's (e.g., Meadows et al., 1972), the concept of sustainability and its cousin sustainable development have become extremely popular across academic, poli;cal, and economic discourses. Despite this popularity and 50 years of publica;ons, a single clear and formal defini;on of sustainability has not emerged. Instead, an ever-growing number of defini;ons have been proposed and applied to myriad topics (Dresner, 2008;Giovannoni and Fabieg, 2014). Among these defini;ons, archaeologists have tradi;onally focused on arguments concerning the longevity of sehlements, especially ci;es and regions in complex socie;es (e.g., Smith, 2010;Smith et al., 2021). Accordingly, they have tended to explore the strategies deployed to maintain socie;es and sehlements for centuries or millennia (